2003
DOI: 10.1029/2003pa000893
|View full text |Cite
|
Sign up to set email alerts
|

Implications of coral reef buildup for the controls on atmospheric CO2 since the Last Glacial Maximum

Abstract: [1] We examine the effect on atmospheric CO 2 of the occurrence of increased shallow water carbonate deposition and regrowth of the terrestrial biosphere following the last glacial. We find that contrary to recent speculations that changes in terrestrial carbon storage were primarily responsible for the observed $20 ppmv late Holocene CO 2 rise, a more likely explanation is coral reef buildup and other forms of shallow water carbonate deposition during this time. The importance of a responsive terrestrial carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(142 citation statements)
references
References 58 publications
9
133
0
Order By: Relevance
“…We prescribed a constant accumulation of carbonates on the tropical shelves of 15.5 Tmol/a, produced by coral reef growth and general accumulation on the shelves, for example through shelf bioherms. The magnitude of this forcing is in line with the estimate by Milliman [1993] and the model value by Ridgwell et al [2003], but higher by about 5 Tmol/a than the estimate used by Kleypas [1997].…”
Section: Model Initialization and Experimentssupporting
confidence: 86%
“…We prescribed a constant accumulation of carbonates on the tropical shelves of 15.5 Tmol/a, produced by coral reef growth and general accumulation on the shelves, for example through shelf bioherms. The magnitude of this forcing is in line with the estimate by Milliman [1993] and the model value by Ridgwell et al [2003], but higher by about 5 Tmol/a than the estimate used by Kleypas [1997].…”
Section: Model Initialization and Experimentssupporting
confidence: 86%
“…The "coral reef hypothesis" [Berger, 1982;Opdyke and Walker, 1992] states that episodic flooding of continental shelves during postglacial sea level rise led to dramatic increases in CaCO 3 production, which released significant amounts of CO 2 to the atmosphere (by a process explained in section 2.1). Recent modeling efforts attest to the importance of this mechanism [Ridgwell et al, 2003]. …”
Section: Overall Importance Of Caco 3 In Marine Carbon Cyclementioning
confidence: 99%
“…Using the forward modelling approach, Ridgwell et al (2003) used estimates of deep ocean carbonate ion con-centrations to constrain the carbon cycle. They found that the observed trend in atmospheric CO 2 during the last 8000 years can best be explained by the build-up of coral reefs and other forms of shallow-water carbonate deposition.…”
Section: Introductionmentioning
confidence: 99%